Use of papain to improve adhesion of hypomineralized enamel in orthodontics, a narrative review - Torres Lefián, Constanza (2024)
Introduction: Correct adhesion is a fundamental part of any orthodontic treatment. There are qualitative enamel alterations such as dental fluorosis, molar incisor hypomineralization and amelogenesis imperfecta that provide hypomineralized enamel in which a good adhesive bond is difficult to achieve. To overcome this difficulty, several alternatives have been proposed, such as the use of deproteinizing agents. The objective of this narrative review is to describe the use of papain as a deproteinizing agent to improve the adhesion of hypomineralized enamels in orthodontics. Materials and methods: A bibliographic search was carried out in PubMed for the last 5 years (2018 - 2023). 77 articles were found, of which 14 met the required criteria and were selected for this review. Results: Enamel deproteinization with papain as a prior enamel conditioning step is a useful alternative during the cementation of fixed orthodontic appliances in hypomineralized enamel. Conclusion: The use of 10% papain is a safe and effective method to improve adhesion in hypomineralized enamel in orthodontics.